Digital Assessment Model of Industrial Practice On-the-job Performance of Social Workers at a Family Learning Center - Yoyoh Jubaedah; Nenden Rani Rinekasari; Neni Rohaeni; Shofa Fithriturrohmi Yusuf (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
The industrial practice assessment tool that can objectively measure the competency achievements of students of the Family Welfare Education Study Program during Industrial Practice at the Family Learning Center (PUSPAGA) is essential. The research objectiveis to produce a digital assessment model for Industrial Practices on the job performance of the social worker. The study used a qualitative descriptive method through expert judgment and the limited availability of exams and responses. Participants are industry practitioners, PUSPAGA external consultants, and a team of government agency experts. Researchers collect data Research results show that a digital assessment model on the job performance of social workers is very feasible to implement and achieve student performancein the implementation of Industrial Practices at PUSPAGA; all of them are declared competent.External Mentors on Industry Practice as a digital assessment user t responds strongly agree thatthe digital assessment model on the job performance of socialworkers is the application: (a) which makes it easier to assess student performance objectively online; (b) more practical, systematic, and efficient in assessing practicum performance; (c) who helps and provides user satisfaction in providing an objective assessment of practicum performance.